Discovery, Yield Improvement, and Application in Marine Coatings of Potent Antifouling Compounds Albofungins Targeting Multiple Fouling Organisms - She, Weiyi; Ye, Wei; Cheng, Aifang; Ye, Wenkang; Ma, Chunfeng; Wang, Ruojun; Cheng, Jinping; Liu, Xuan; Yuan, Yujing; Chik, Sin Yu; Limlingan Malit, Jessie James; Lu, Yanhong; et al. (Frontiers in Microbiology, 2022)
Marine biofouling caused huge economic losses of maritime industries. We aim to develop high-efficient, less-toxic, and cost-effective antifoulants to solve the problems of biofouling. In this study, we described the antifouling compounds albofungin and its derivatives (albofungin A, chrestoxanthone A and choloalbofungin) isolated from the metabolites of bacterium Streptomyces chrestomyceticus BCC 24770, the construction of high-yield strains for albofungin production, and application of albofungin-based antifouling coatings. Results showed that these albofungins have potent antibiofilm activities against Gram-positive and Gram-negative bacteria and anti-macrofouling activities against larval settlement of major fouling organisms with low cytotoxicity. With the best antifouling activity and highest yield in bacterial culture, albofungin was subsequently incorporated with hydrolysable and degradable copolymer to form antifouling coatings, which altered biofilm structures and prevented the settlement of macrofouling organisms in marine environments. Our results suggested that albofungins were promising antifouling compounds with potential application in marine environments.